Information Mediation Practices in Algerian Academic Libraries - Abdelghani Bendridi (Informatio, 2024)
This paper investigates information mediation practices in Algerian academic libraries, with a case study of Mohamed Lamine Debaghine Setif 2 University. It aims to explore librarians' understanding of information mediation concepts and principles, as well as the challenges and opportunities for improvement.